Eksistensi Kajian Kitab Kuning di Era Digital (Studi Pada Pondok Pesantren Riyadlusharfi Walmantiq di Kabupaten Pangandaran) - Azzulfa, Fatihatul Anhar; Tsani, Wifa Lutfiani; Suryani, Irma Kartika (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
This article explores the presence of the yellow book learning model at Islamic boarding schools amidst the rapid digitalization era. The transition from the traditional model to the digital age is highlighted by the emergence of various literary works in the form of e-books, PDFs, or applications on the Play Store that feature the yellow book along with translations. This learning model is thought to present its own challenges in addition to the classical method, allowing it to remain relevant among students. The research is categorized as field research with a qualitative approach. Data collection methods include observation, interviews, documentation studies, and literature reviews. The findings indicate that the Riyadlusharfi Walmantiq Islamic Boarding School, in adapting to the digital era, has maintained a modern traditional style using methods such as sorogan, bandongan, bahtsul masail, memorization (muḥāfaẓah), worship practices, and mudzakarah. The challenge of preserving the classical method is quite complex due to the ongoing advancements in science and technology, yet the classical method is regarded as the best way to transfer knowledge from the yellow book to students.